Size Effect in Market-wide Liquidity Commonality: Evidence from the Indian Stock Market - Cheriyan, Namitha K.; Lazar, Daniel (Organizations and Markets in Emerging Economies, 2019)
Liquidity commonality and the co-movements in trading costs related to such commonality have remarkable implications in market microstructure. Analyzing and identifying such commonality will enable the investor and policy maker to discover evidence regarding the inventory risks and asymmetric information in uencing individual securities’ liquidity. Thus, this study aims at documenting the liquidity commonality and measuring its extent in the Indian stock market. Employing fourteen liquidity measures a ributed to the cost, quantity, time, and multidimensional aspects of liquidity, it empirically proves the existence of co-movements among market-wide liquidity and the individual securities’ liquidity. The study also shows the presence of a size effect in liquidity commonality in Indian stock market. It is found that the slope coefficient indicating the interface between market-wide liquidity and individual securities’ liquidity generally increases with size.
Keywords: liquidity; ommonality in liquidity; NIFTY 50; liquidity measures